2011
DOI: 10.1002/pat.2002
|View full text |Cite
|
Sign up to set email alerts
|

Two‐photon microfabrication of poly(ethylene glycol) diacrylate and a novel biodegradable photopolymer—comparison of processability for biomedical applications

Abstract: Two‐photon polymerization (2PP) is a versatile microfabrication tool for biomedical applications as it provides unparalleled resolution for accurate three‐dimensional (3D) replication of biological microstructures. To widen the selection of biomaterials suitable for 2PP, this paper presents the processing of a methacrylated poly(ε‐caprolactone)‐based oligomer (PCL‐o) and a poly(ethylene glycol) diacrylate (PEGda) hydrogel into microstructures. PCL‐o is a novel biodegradable photopolymer that has not been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Fibroblasts, cultured onto spin-coated thin films after photopolymerization, remained viable and showed comparable cell attachment and division regarding cells cultured on glass surfaces (control), which indicates that the developed material do not affect cell proliferation. In a similar work, Koskela et al [53] used the 2PP technique to produce [31] microstructures, using methacrylated PCL-based oligomer (PCL-o) and Irgacure ® 127 as UV photoinitiator. Live/dead staining analysis showed that hESC-derived neuronal cells, cultured on the PCL film for 7 days, were able to attach to the surface, though the material did not allow cell migration.…”
Section: Synthetic Polymers and Hydrogelsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fibroblasts, cultured onto spin-coated thin films after photopolymerization, remained viable and showed comparable cell attachment and division regarding cells cultured on glass surfaces (control), which indicates that the developed material do not affect cell proliferation. In a similar work, Koskela et al [53] used the 2PP technique to produce [31] microstructures, using methacrylated PCL-based oligomer (PCL-o) and Irgacure ® 127 as UV photoinitiator. Live/dead staining analysis showed that hESC-derived neuronal cells, cultured on the PCL film for 7 days, were able to attach to the surface, though the material did not allow cell migration.…”
Section: Synthetic Polymers and Hydrogelsmentioning
confidence: 98%
“…However, 2PP systems are very expensive, operating with a single material type that prevents the fabrication of multimaterial constructs [85]. These equipments usually employ a femtosecond titanium:sapphire laser (short pulse width and high peak power) without photo-masks, operating at approximately 800 nm wavelength to induce the polymerization [53,74,82]. A great variety of natural and synthetic photosensitive materials can be used for the 2PP technique, like acrylate-based polymer, zirconium sol-gels, organically modified ceramic materials, aliphatic polyesters and gelatin [52,74,79,105].…”
Section: Stereolithographymentioning
confidence: 99%
See 1 more Smart Citation
“…The most common biomaterials for 2PP stereolithography include gelatin [159], hyaluronic acid [160], PEG [161], PCL [162] and PLA [163]. The capabilities of 2PP stereolithography for the fabrication of 3D cellular hydrogels were also shown by the direct printing of gelatin methacrylamide containing human osteosarcoma cells [159].…”
Section: Two-photon Polymerization (2pp) Stereolithographymentioning
confidence: 98%
“…For example, human embrionic stem cell (hESC)-derived neuronal cells cultured on PEGDA or a poly( P -caprolactone)-based oligomer (PCL-o) were able to attach on both material surfaces, but did not migrate. 103 Only the cells placed inside the structures survived, whereas the ones found outside the scaffolds were dead. Aer a subsequent material functionalization, PEGDA and PCL-o could be used as guidance structures in neural cell culture applications.…”
mentioning
confidence: 99%